Researches on efficient transmission protocol for multi-cell system based on interference toleration - Bao-feng JI; Chun-guo LI; Kang SONG; Yi WANG; Liang SONG (Tongxin xuebao)
A two-time-slot transmission protocol was designed according to the cell-edge users' interference problem.The precoder closed expressions under the proposed transmission protocol were derived based on the well-known precoder scheme of the signal-to-leakage-plus-noise ratio(SLNR).Furthermore,an adaptive receiver was based on the non-linear minimum mean square error criterion.Simulation results demonstrated that the proposed transmission protocol has significant sum-rate gains compared with traditional system.